Mathematical modelling of the stress-train state of the hip joint with different values of the cervicodiaphyseal angle - Zelenetsky, Ivan; Yaresko, Oleksandr; Miteleva, Zoya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
A relationship between changes in the cervicodiaphyseal angle and stress in the femoral head and neck was assessed with help of the finite element method. It was revealed that a change of the cervicodiaphyseal angle from 120º to 160º resulted in increases of the stress-train state and stress concentration area along the superior and inferior surfaces of the proximal femur versus the normal angle. A higher stress produced an excess pressure on vessels in the femoral neck, thereby later possibly causing bone tissue dystrophy in the femoral head.